Visual evoked potential changes in patients with diabetes mellitus without retinopathy - Gupta, Sangeeta; Gupta, Gaurav; Deshpande, V.K. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus is a metabolic disorder, associated with a great deal of morbidity in the patients due its chronic complications including diabetic retinopathy. Visual evoked potentials (VEPs), which assess the functional integrity of the visual functions from retina to visual cortex, can prove to be a sensitive tool to study the possible effects that diabetes may exert on the visual system. In patients without clinically evident retinopathy, electrophysiological evidence of visual dysfunction can help in early detection of the visual involvement. Hence, this study attempted to detect the presence of such visual dysfunctions in the diabetics without retinopathy by pattern- reversal visual evoked potentials (PRVEPs). Methods: PRVEP was recorded in 116 subjects (64 diabetics without retinopathy and 52 controls). P100 latency, N75-P100 amplitude and interocular latency differences were compared between the diabetics and the controls. The parameters were compared among the groups with different duration of the disease as well as those with different glycaemic status. Results: The study has demonstrated significant prolongation of mean P100 latency, reduction in N75-P100 amplitudes and increased interocular latency difference in the diabetics as compared to the control group. The duration of the illness was found to alter the mean P100 latency while the glycaemic status of the diabetics was not found to be correlated with the PRVEP abnormalities. Conclusions: VEP responses are deranged in diabetic patients before the development of retinopathy. VEP measurements can be used for the early diagnosis of visual dysfunctions in the diabetes for a better prognosis of the condition.